2018
DOI: 10.5489/cuaj.4781
|View full text |Cite
|
Sign up to set email alerts
|

Case ‒ Laparoscopic transperitoneal partial nephrectomy of T3a renal cell carcinoma within a horseshoe kidney

Abstract: Horseshoe kidney (HSK) is a benign malformation characterized by three anatomic abnormalities: ectopia, malrotation, and vascular changes.1 Renal cell carcinoma (RCC) comprises approximately 53.8% of HSK malignancies. The incidence of RCC within HSK is predicted to equal that within the general population, approximately 5.2/100 000 individuals.2-4 Surgical resection of these tumors has been described in the literature. Evidence is mounting that partial nephrectomy, rather than radical nephrectomy, and minimall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In fact, performance of laparoscopic partial nephrectomy for a renal mass has only been reported in seven patients with HSK. [7][8][9] The tumors ranged from 2 to 6.9 cm in diameter, WIT was 11-31 min, and estimated blood loss was 70-490 mL. Major complications were not reported in these patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, performance of laparoscopic partial nephrectomy for a renal mass has only been reported in seven patients with HSK. [7][8][9] The tumors ranged from 2 to 6.9 cm in diameter, WIT was 11-31 min, and estimated blood loss was 70-490 mL. Major complications were not reported in these patients.…”
Section: Discussionmentioning
confidence: 89%
“…Several anatomical features of HSK make laparoscopic partial nephrectomy challenging, including variability of the blood supply, limited mobilization of the fused kidney, and abnormal anatomy of the kidneys and adjacent structures. In fact, performance of laparoscopic partial nephrectomy for a renal mass has only been reported in seven patients with HSK . The tumors ranged from 2 to 6.9 cm in diameter, WIT was 11–31 min, and estimated blood loss was 70–490 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Horseshoe kidney is a congenital benign malformation present in the population at a rate of 0.15–0.25% and is characterized by anatomical abnormalities such as ectopia, malformation and vascular changes 1 . The incidence of renal cell carcinoma in horseshoe kidneys is estimated to equal that in normal kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…According to our online literature review, few such cases have been reported to date. [7][8][9][10][11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%